3D printing of conductive elastomers for wearable strain sensors - Lau, Ka Yan (Nanyang Technological University, 2024)
The primary goal of this research is to fabricate conductive elastomers using the advanced capabilities of Multi Jet Fusion (MJF) 3D printing technology. Utilizing thermoplastic polyurethane (TPU) powder and a commercially available Fusing agent (FA) that contains carbon black (CB), the study dives into the exploration of modifying fusing agent layers to control the electrical conductivity and piezoresistive response of the printed parts. When subjected to mechanical stimuli such as bending and twisting, the printed parts showcased a significant adaptability in their electrical properties, enabling their application in dynamic sensing devices. The empirical analysis confirmed that the electrical resistance of the TPU-based constructs could be fine-tuned by adjusting the number of fusing agent layers, thereby endowing the material with a tailored electrical response suitable for varied sensing applications. Our investigation revealed that the 3D-printed strips exhibited reliable performance in sensing different deformation scenarios, including varying directions and deformation speeds, thereby underscoring their potential integration into the domain of flexible electronics. These applications span across several crucial sectors, including but not limited to health monitoring, robotics, and structural integrity assessment. The strategic use of commercially viable materials like TPU and CB-contained fusing agents underscored the economic feasibility of this method, emphasizing the potential for scaling production and broadening the for more research utilizing the shape memory polymer (SMP) property TPU parts have. The successful outcome of this research not only highlights the scalability and vast application spectrum of flexible electronics but also marks a significant step towards the transformation of printed electronics from laboratory research to actual commercial products. By demonstrating the versatile, responsive nature of the materials produced through MJF technology, this study lays the groundwork for the upcoming expansion of printed electronics, setting the stage for their practical application and market readiness. The prospects for MJF in crafting multifunctional, responsive materials appear promising, signalling a new era in the application of conductive elastomers.